Peran Smart City dalam Menentukan Pergerakan Penduduk Kota Sebelum dan Sesudah Pandemi Covid-19 di Kota Surabaya - Putri, Shinta Permana (Mahesa Research Center, 2023)
This article aims to describe changes in citizens' movement during the Covid-19 and determine the role of smart cities in influencing these changes. The main ploblem in this research is the emergence of Covid-19 which has had an impact on hindering the movement of citizens' activities. In this case, not all cities in Indonesia that implement smart cities can handling this impact. This research was conducted using a mix-methods. The data was collected through questionnaires and secondary data. This data was then analyzed quantitatively and qualitatively. This research concludes that the emergence of Covid-19 has had its own impact on the activities of Surabaya citizens'. Even though in general the significant impact only occurs on educational activities, the capacity of citizens to implement digital transformation accelerated by the emergence of Covid-19 still needs to be improved. With the implementation of smart cities in the city of Surabaya, it actually plays a role in overcoming the negative path of Covid-19 in the movement of population activities. Even so, the optimal application of smart cities in handling Covid-19 in the Surabaya still depends on its citizens. In this case, citizens must ensure their involvement and activeness in using and developing these innovations. For the Surabaya City government, smart city development still needs to be carried out, especially in the dimensions of smart people, smart mobility, smart environment and smart economy.